Recent Advances in Membrane Shaping for Plant Autophagosome Biogenesis - Wun, Cheuk-Ling; Quan, Yingfei; Zhuang, Xiaohong (Frontiers in Plant Science, 2020)
Autophagy is an intracellular degradation process, which is highly conserved in eukaryotes. During this process, unwanted cytosolic constituents are sequestered and delivered into the vacuole/lysosome by a double-membrane organelle known as an autophagosome. The autophagosome initiates from a membrane sac named the phagophore, and after phagophore expansion and closure, the outer membrane fuses with the vacuole/lysosome to release the autophagic body into the vacuole. Membrane sources derived from the endomembrane system (e.g., Endoplasmic Reticulum, Golgi and endosome) have been implicated to contribute to autophagosome in different steps (initiation, expansion or maturation). Therefore, coordination between the autophagy-related (ATG) proteins and membrane tethers from the endomembrane system is required during autophagosome biogenesis. In this review, we will update recent findings with a focus on comparing the selected core ATG complexes and the endomembrane tethering machineries for shaping the autophagosome membrane in yeast, mammal, and plant systems.